Stretchable MXene/Thermoplastic Polyurethanes based Strain Sensor Fabricated Using a Combined Electrospinning and Electrostatic Spray Deposition Technique - Fang, Feiyu; Wang, Han; Wang, Huaquan; Gu, Xiaofei; Zeng, Jun; Wang, Zixu; Chen, Xindu; Chen, Xin; Chen, Meiyun (Micromachines (Basel), 2021)
In this work, a novel flexible electrically resistive-type MXene/Thermoplastic polyurethanes(TPU) based strain sensors was developed by a composite process of electrospinning (ES) and electrostatic spray deposition (ESD). Compared with other deposition processes, the sensing layer prepared by ESD has better adhesion to the ES TPU nanofiber membrane and is not easy to crack during the stretching process, thereby greatly improving the working range of the strain sensor. Furthermore, we obtained the sandwich structure easily by ES on the surface of the sensing layer again. This will help make the stress distribution more uniform during the stretching process and further increase the strain sensing range. The ESD-ES strain sensors were attached on skin to monitor various human motions. The results demonstrate that our ESD-ES strain sensors have wide application prospects in smart wearable device.